2020
DOI: 10.1161/jaha.119.014264
|View full text |Cite
|
Sign up to set email alerts
|

Relative Change of Protidemia Level Predicts Intradialytic Hypotension

Abstract: Background Hemodialysis patients are at risk of intradialytic hypotension ( IDH ), which is associated with mortality and cardiovascular and neurological events. The use of biomarkers of volemia such as relative change in protidemia and BNP (B‐natriuretic peptide) levels to predict IDH remains unknown. Methods and Results We conducted a prospective observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Some of them also included serum biomarkers in the analysis to improve accuracy. Assayag et al (2020) analyzed B-natriuretic peptide using a logistic mixed model to predict the 30-day risk of IDH. The accuracy was still not satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them also included serum biomarkers in the analysis to improve accuracy. Assayag et al (2020) analyzed B-natriuretic peptide using a logistic mixed model to predict the 30-day risk of IDH. The accuracy was still not satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“… Ozen and Cepken (2020) found that white blood cell (WBC) values were significantly higher in patients developing IDH. The difference between post-dialysis protidemia and pre-dialysis protidemia outperformed BNP (B-natriuretic peptide) and ultrafiltration rate as a predictor for the 30-day risk of IDH ( Assayag et al, 2020 ). Nephrologists still seek a simplified and readily available method, especially in the HD setting, when many patients start treatments while waiting for ultrafiltration prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we could not assess to what extent hypovolaemia and dysautonomia contribute to the pathophysiology of IDH. Our current practice to prevent IDH also includes the adjustment of the dry weight according to the ΔProtidaemia, which is assessed monthly and could reduce the frequency of IDH in our population during the follow-up [ 25 ]. The association between pre-dialysis HD ESC and IDH was only significant after 45 days.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found potential predictors of IDH, such as TNF-α, IL-1 β [17] , propeptide level (Δ Prot) [18], Δ OER (oxygen uptake rate) [19], coronary artery calcium score (CACS) [20] and so on. Studies have shown that Δ OER > 19% 15 minutes after the start of dialysis or > 36% final increment at the end of dialysis can help identify high-risk IDH patients with hemodynamic instability, but this method can only be applied to patients with permanent central venous catheters [19].…”
Section: Biomarkers and Potential Predictorsmentioning
confidence: 99%